Developments in Machining of Stacked Materials Made of CFRP and Titanium/Aluminium Alloys - Pramanik, Alokesh; Littlefair, G. (Taylor and Francis, 2014)
The aim of this paper is to investigate the drilling of carbon fibre reinforced plastic (CFRP) composite/metal stack-ups to have a details picture of the developments in this complex area. The forces and torque, chip shape, surface finish and geometry, and tool material and tool wear for drilling composite/metal stack-ups have been analysed in details in addition to drilling mechanism of CFRP. The relation between input and output parameters was discussed and the trend of input parameters for damage free and tight tolerance holes has been investigated based on the literature. The main findings are (i) heat, built-up edge and chips generated from drilling of metallic layers damages CFRP surface, (ii) order of material layers affects the drilling outcomes significantly, (iii) coatings and step-shape on the cutting tool improves the tool performance, (iv) tool materials should be selected based on the material of metallic layer, (v) chipping, adhesion, abrasion and attrition are main tool wear mechanism during machining of CFRP/metal stacks and (vi) application of coolant improves the machinability.